2021
DOI: 10.3390/en14175423
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Single- vs. Two-Stage Process for the Anaerobic Digestion of Liquid Cow Manure and Cheese Whey

Abstract: The growing interest in processes that involve biomass conversion to renewable energy, such as anaerobic digestion, has stimulated research in this field in order to assess the optimum conditions for biogas production from abundant feedstocks, like agro-industrial wastes. Anaerobic digestion is an attractive process for the decomposition of organic wastes via a complex microbial consortium and subsequent conversion of metabolic intermediates to hydrogen and methane. The present study focused on the exploitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
(68 reference statements)
3
10
0
Order By: Relevance
“…Prior to its use as feeding material, ES was subjected to alkaline pretreatment at 80 • C for 2 h by adding an alkaline solution consisting of 0.5% NaOH and 0.5% KOH (w/w dry matter). The chemical composition of all substrates was in accordance with other studies found in the literature [7,28,42].…”
Section: Chemical Composition Of Each Substratesupporting
confidence: 90%
See 3 more Smart Citations
“…Prior to its use as feeding material, ES was subjected to alkaline pretreatment at 80 • C for 2 h by adding an alkaline solution consisting of 0.5% NaOH and 0.5% KOH (w/w dry matter). The chemical composition of all substrates was in accordance with other studies found in the literature [7,28,42].…”
Section: Chemical Composition Of Each Substratesupporting
confidence: 90%
“…In particular, co-digestion is considered to be an appealing option for boosting the efficiency of the process thanks to its positive synergisms which can significantly increase the economic viability of biogas plants [5]. Furthermore, two-stage anaerobic digestion exhibits various benefits compared to the conventional one-stage process, as it enables the selection and the enrichment of Fermentation 2022, 8, 304 2 of 15 microflora in the reactors, enhancing the stability of the system by (a) the acidification phase regulation in the first reactor and (b) overloading and/or preventing inhibition of the methanogenic population in the second reactor [6,7]. At the first stage of acidogenesis, generation of biological hydrogen and various soluble metabolites takes place, whereas at the second stage the methane is produced [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pH of the inoculum being more than 7 also adds that the digestate is stable and falls within the range of methanogenic bacterial growth [41,42]. The methane composition of the produced gas is very low suggests that the peak of the first three days is of fermentation via acidogenesis and acetogenesis, and largely represents hydrogen production [43,44]. The methane percentage is seen to increase to a maximum of 94.74% on the 22nd day of the tests.…”
Section: Effect Of S:i Ratios On Biogas Production Kineticsmentioning
confidence: 95%